English Derivational and Inflectional Morphemes of the Authentic-Recount Text - Anisa Fajriati; Senowarsito; Ardini, Sukma Nur (SALEE: Study of Applied Linguistics and English Education, 2024)
Some first-grade students of SMKN 1 Pemalang still have difficulties in arranging words when they produce texts. Vocational students generally focus more on their vocations such as computer network engineering, visual communication design, etc. This impacts their ability to string words in English related to applying derivational and inflectional morphemes because they are meaningful in composing sentences according to their meaning and function. So, this research aimed to discover the types and errors of derivational and inflectional morphemes found in the authentic-recount texts made by vocational students. Fromkin’s theory was used to analyze data using descriptive qualitative method. It revealed 5 types of derivational and 3 types of inflectional morphemes were used by students when creating authentic-recount texts. Additionally, learners still make errors in applying those morphemes into sentences of the recount texts with a total of 38 errors, including 5 derivational morphemes and 33 inflectional morphemes. Thus, students are required to understand more about the function and meaning of words before constructing sentences because it plays a significant part in writing English texts. Further researchers are advised to conduct deeper research that focuses on reconstructing sentences, especially in implementing suffixes or other materials which are included in morphology subject.